Study on parameter measurement of elastic thin films with substrate effect based on contact mechanics. (1st June 2023) - Zhang, Wen-Hua
Highlights: The solutions of three contact forms (spherical, conical, and cylindrical contact) expressed by elementary functions in two structural forms ("film with two free boundaries" and "film/rigid substrate") are presented. The influence law of "substrate effect" on indentation curve is analyzed. Poisson's ratio has little influence on P z - a curve, which is affected by elastic modulus a lot. The measurement method of thin film material parameters is given with considering substrate effect. Abstract: The development of contact theories for films is valuable for high-precision machining and measurement. Accordingly, accurate contact mechanics theories for films under common indenter loading are established based on the constitutive equations and potential theory method, Here, the film structures are "film with two free boundaries" and "film/rigid substrate." The displacement and stress at arbitrary positions can be obtained using exact solutions represented by elementary functions. The application of the foregoing theories to resolve the contact problem encountered in films is convenient for engineers. The influences of substrate and film parameters on contact radius and indentation depth were analyzed. Indentation curves are slightly influenced by Poisson's ratio, but primarily affected by the elastic modulus. An effective method for measuring of film material parameters is presented. Using numerical software platforms, the method's analytic algorithm can be transformed into numerical codes and be integrated into special software.